Advances in agronomy. - Sparks, Donald L., 1953- (Academic Press, 2019)
Advances in Agronomy, Volume 157, continues to be recognized as a leading reference and first-rate source for the latest research in agronomy. Each volume contains an eclectic group of reviews by leading scientists throughout the world. As always, the subjects covered are rich, varied, and exemplary of the abundant subject matter addressed by this long-running serial. Key Features: Includes numerous, timely, state-of-the-art reviews on the latest advancements in agronomy; Features distinguished, well recognized authors from around the world; Builds upon this venerable and iconic review series; Covers the extensive variety and breadth of subject matter in the crop and soil sciences. Readership: Scientists and practitioners in academe, government, and industry and students in an array of fields including crop and soil sciences, agronomy, plant biology, and environmental sciences. --